2022
DOI: 10.1001/jamacardio.2022.3627
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serial High-Sensitivity Cardiac Troponin T With Subsequent Cardiovascular Events in Patients Stabilized After Acute Coronary Syndrome

Abstract: ImportanceStudies have demonstrated an association between single measures of high-sensitivity troponin (hsTn) and future cardiovascular events in patients with chronic coronary syndromes. However, limited data exist regarding the association between changes in serial values of hsTn and subsequent cardiovascular events in this patient population.ObjectiveTo evaluate the association between changes in high-sensitivity troponin T (hsTnT) and subsequent cardiovascular events in patients stabilized after acute cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
4
1
Order By: Relevance
“…In fact, only 3% of our patients showed a relative hs‐cTnT increase of >25% during the 30‐day to 1‐year study period (based on the linear mixed‐effects model; data not shown). The findings in BIOMArCS contrast with previous reports by White et al, 30 Everett et al, 31 Cavender et al, 32 and Patel et al, 33 who reported a meaningful increase in cardiac troponin in up to 23% of patients with coronary artery disease and increasing concentrations were associated with a worse prognosis in all 4 studies. Indeed, increasing cardiac troponin concentrations are disconcerting, as these are potentially related to ongoing myocyte necrosis, chronic processes related to left ventricular hypertrophy, 34 , 35 increasing renal dysfunction, 36 or poor diabetes control.…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…In fact, only 3% of our patients showed a relative hs‐cTnT increase of >25% during the 30‐day to 1‐year study period (based on the linear mixed‐effects model; data not shown). The findings in BIOMArCS contrast with previous reports by White et al, 30 Everett et al, 31 Cavender et al, 32 and Patel et al, 33 who reported a meaningful increase in cardiac troponin in up to 23% of patients with coronary artery disease and increasing concentrations were associated with a worse prognosis in all 4 studies. Indeed, increasing cardiac troponin concentrations are disconcerting, as these are potentially related to ongoing myocyte necrosis, chronic processes related to left ventricular hypertrophy, 34 , 35 increasing renal dysfunction, 36 or poor diabetes control.…”
Section: Discussioncontrasting
confidence: 85%
“…On the other hand, we consider the regression to the mean phenomenon a serious limitation of previous studies that investigated change based on 2 measurements only. 30 , 31 , 32 , 33 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hs-cTn may be an important tool to measure residual CVD risk in secondary prevention [4] , [5] , [6] . The current NHANES results are important as this cohort is designed to be representative of the diverse US adult population and because of the ability to test for any differences in important subgroups (including by sex and race/ethnicity).…”
Section: Discussionmentioning
confidence: 99%
“…Originally designed to expedite the diagnosis of myocardial infarction, high-sensitivity cardiac troponin (hs-cTn) assays have since emerged as prognostic biomarkers associated with cardiovascular disease (CVD) outcomes in a range of settings [1] , [2] , [3] . One of these settings is in the care of adults with a history of CVD who are being managed for secondary prevention [4] , [5] , [6] .…”
Section: Introductionmentioning
confidence: 99%